Taxonomic and functional threshold responses of vertebrate communities in the Atlantic Forest Hotspot. (May 2021) - Anunciação, Paula Ribeiro; Barros, Fabio M.; Ribeiro, Milton Cezar; Carvalho, Luis Marcelo Tavares de; Ernst, Raffael
Abstract: Ecological thresholds are an indicator of rapid and non-linear changes along both natural habitat and land-use gradients. Thus, they can be used to quantify biodiversity responses to human-induced environmental change. We investigated multiple thresholds by analyzing eight environmental predictors of both taxonomic and functional composition of amphibian and bird communities in 47 independent sample units, located within a heterogeneous land use matrix of the megadiverse Atlantic Forest hotspot. We demonstrate that current land use practices alter both the taxonomic and functional composition and promote the establishment of non-native taxa resulting in novel assemblages. Whereas anuran communities experienced dramatic compositional shifts as a result of the transformation of closed forest habitats into Eucalyptus monocultures (at less than 10% land cover), bird communities were mainly altered through the loss of old-growth forest (at 20% forest cover loss). In both groups, observed thresholds were lower than previously reported and much lower than the 20% forest set-aside requirement defined by current land-use legislation. We argue that the strategy of halting forest loss through rapid afforestation with non-native trees has converse and potentially detrimental effects on the conservation of native forest biodiversity. Future studies need to investigate how including novel assemblages in current conservation management strategies can enhance biodiversity protection in human-impacted forest landscapes. The identification of taxon-specific thresholds for both taxonomic and functional community shifts is indispensable when formulating common land use practices and designing mitigation measures. Threshold analyses can guide these actions by providing clear and quantifiable break-points for conservation practitioners. Highlights: Current land-use alters taxonomic and functional composition of frogs and birds in Atlantic Forest. Critical environmental thresholds are lower than expected. Afforestation with Eucalyptus monocultures facilitates invasive species. The current land-use policy in Brazil promotes novel assemblages. Threshold analyses can guide conservation decisions in fragmented landscapes.